The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1165/rcmb.2020-0512oc
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Pyruvate Kinase M2 Promotes Inflammation in a Mouse Model of Obese Allergic Asthma

Abstract: Obesity is a risk factor for the development of asthma and represents a difficult-to-treat disease phenotype. Aerobic glycolysis is emerging as a key feature of asthma, and changes in glucose metabolism are linked to leukocyte activation and adaptation to oxidative stress. Dysregulation of PKM2 (pyruvate kinase M2), the enzyme that catalyzes the last step of glycolysis, contributes to house dust mite (HDM)-induced airway inflammation and remodeling in lean mice. It remains unclear whether glycolytic reprogramm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Their results were independently confirmed by Manuel et al, who showed HDM to trigger PKM2-dependent glycolytic reprogramming and airway inflammation in a murine model of obese allergic asthma and airway epithelial cells [ 38 ]. These results suggest alternative, non-glycolytic functions of PKM2 to exert pro-inflammatory roles in asthma by glutathione-dependent protein oxidation via a putative IFN-γ–glutaredoxin 1 pathway [ 38 ].…”
Section: Disease-specific Findings In Allergymentioning
confidence: 77%
See 1 more Smart Citation
“…Their results were independently confirmed by Manuel et al, who showed HDM to trigger PKM2-dependent glycolytic reprogramming and airway inflammation in a murine model of obese allergic asthma and airway epithelial cells [ 38 ]. These results suggest alternative, non-glycolytic functions of PKM2 to exert pro-inflammatory roles in asthma by glutathione-dependent protein oxidation via a putative IFN-γ–glutaredoxin 1 pathway [ 38 ].…”
Section: Disease-specific Findings In Allergymentioning
confidence: 77%
“…Asthma is a complex disease comprising different phenotypes that are characterized by airway-inflammation, -remodeling, and -hyperreactivity. Studies have repeatedly shown the presence of metabolic anomalies in asthmatic patients and many metabolic pathways, including glycolysis [36][37][38][39][40], amino acid metabolism [41,42], fatty acid metabolism [43,44], and sphingosine metabolism [45][46][47],…”
Section: Asthmamentioning
confidence: 99%
“…Moreover, recent insights suggest SRT2104's anti-inflammatory effects may be partially attributed to modulating pyruvate kinase M2 (PKM2), a key inflammatory regulator in conditions such as sepsis, asthma, and encephalomyelitis. Elevated PKM2 levels during inflammation can be counteracted by autophagy [118][119][120] , highlighting another potential mechanism for SRT2104's therapeutic action.…”
Section: Clinical Trialmentioning
confidence: 99%
“…A growing body of evidence suggests that metabolic reprogramming would be actively involved in the orchestration of metabolic processes and inflammatory responses under various pathological circumstance including critical illness, metabolic syndrome, tumor, et al ( Mazumdar et al, 2020 ). Pyruvate kinase M2 (PKM2), a key enzyme in the last step of glycolysis, has been regarded as a crucial regulator in inflammatory diseases such as sepsis, asthma as well as encephalomyelitis ( Yang et al, 2014 ; Damasceno et al, 2020 ; Manuel et al, 2021 ). PKM2 is significantly upregulated in inflammatory response, which promotes the expression of pro-inflammatory genes via a diverse of mechanisms ( Yang et al, 2014 ; Palsson-McDermott et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%